A Confession of Female Smokers in Medan about Their Smoking Habit (Cigarette and Chewing Tobacco): A Preliminary Study - Miskah Afriani; Yuzana Binti Mohd Yusop; Harmy Bin Muhamed Yusof (RIRAI Publisher, 2020)
Indonesia is the country with the highest number of smokers in ASEAN, with 65.19 million people. Equivalent is 34% of the total population of Indonesia in 2016. As 2545 women smoke, they smoke in various types, such as cigarettes, chewing tobacco, and vape (SDKI, 2018). Smoking prevalence among women is lower than that for men in most countries, but the rate is increasing rapidly from 4.2 percent to 6.7 percent in 2010-2013 (Riskesdas,2013).This research used qualitative approach. Semi-structured interviews were held with 47 individuals from Medan city. A purposive sample was used who self-identified as female smokers in the past 30-days. Most of the participants who volunteered to take part in the study were over 25 years old. Tobacco users are divided into two focal categories which are cigarette smokers and chewing tobacco addicts, 31 reported as cigarette smokers, and 16 were reported having a chewing tobacco habit. Researches categorized cigarette users or smokers as CU and chewing tobacco users as CTU. The analysis of transcripts from the interviews revealed five main themes: 1) Personal problem lead to smoking (CU) 2) School friends’ influences initiate the habit (CU) 3) Family tradition originate the chewing tobacco habit (CTU) 4) Prevent egoistic status from the tribe (CTU) and 5) Intent and struggle to quit but unsuccessful for CU but not CTU. Acclimatizing health promotion awareness and activities shall be concentrate on such as oral health, quit smoking and chewing tobacco program as well as motivational improvement approach to quit the smoking